We don't want your water: Broadening community understandings of and engagement in flood risk and mitigation - Skilton, Liz; Osland, Anna C.; Willis, Emma; Habib, Emad H.; Barnes, Stephen R.; ElSaadani, Mohamed; Miles, Brian; Do, Trung Quang (Frontiers in Water, 2022)
Many communities across the USA and globally lack full understanding of the flood risk that may adversely impact them. This information deficit can lead to increased risk of flooding and a lack of engagement in mitigation efforts. Climatic changes, development, and other factors have expedited changes to flood risk. Due to these changes, communities will have an increased need to communicate with a variety of stakeholders about flood risk and mitigation. Lafayette Parish, Louisiana, USA, having recently experienced a major flood event (the 2016 Louisiana Floods), is representative of other communities experiencing changes to flood impacts. Using focus groups, this study delves into better understanding the disconnect between individual and community perceptions of flood risks, and how emerging hydroinformatics tools can bridge these gaps. Using qualitative analysis, this study evaluated the resources individuals use to learn about flooding, how definitions of community impact flood mitigation efforts, how individuals define flooding and its causes, and where gaps in knowledge exist about flood mitigation efforts. This research demonstrates that individuals conceive of flooding in relationship to themselves and their immediate circle first. The study revealed division within the community in how individuals think about the causes of flooding and the potential solutions for reducing flood risk. Based on these results, we argue that helping individuals reconceive how they think about flooding may help them better appreciate the flood mitigation efforts needed at individual, community, and regional levels. Additionally, we suggest that reducing gaps in knowledge about mitigation strategies and broadening how individuals conceive of their community may deepen their understanding of flood impacts and what their community can do to address potential challenges.